Pengaruh Pendanaan Eksternal dan Inovasi Produk terhadap Pertumbuhan Usaha - Abdul Kohar; Moh. Tahang (Jurnal Riset dan Inovasi Manajemen, 2023)
This study aims to investigate the effect of external funding and product innovation on entrepreneurial business growth. The research method used is a descriptive qualitative approach. This research was conducted over a two-month period spanning from May to June of 2023. The results showed that external funding plays a significant role in supporting entrepreneurial business growth. Funds obtained from external sources, such as venture investment or bank loans, enable entrepreneurial ventures to expand operations, increase production, and develop market share. In addition, product innovation also has a positive influence on the growth of entrepreneurial ventures. Companies that are able to produce innovative new products or services can attract new customers, increase customer loyalty, and increase revenue. The limitations of this study are the limited data available in the research period and the focus on entrepreneurial companies in one particular sector. The implication of this study is that it is important for entrepreneurs to consider external funding as a potential source of financing and also encourage product innovation as a strategy to achieve sustainable business growth.